LLM Performance in Low-Resource Languages: Selecting an Optimal Model for Migrant Integration Support in Greek - Alexandros Tassios; Stergios Tegos; Christos Bouas; Konstantinos Manousaridis; Maria Papoutsoglou; Maria Kaltsa; Eleni Dimopoulou; Thanassis Mavropoulos; Stefanos Vrochidis; Georgios Meditskos (Future Internet)
The integration of Large Language Models (LLMs) in chatbot applications gains momentum. However, to successfully deploy such systems, the underlying capabilities of LLMs must be carefully considered, especially when dealing with low-resource languages and specialized fields. This paper presents the results of a comprehensive evaluation of several LLMs conducted in the context of a chatbot agent designed to assist migrants in their integration process. Our aim is to identify the optimal LLM that can effectively process and generate text in Greek and provide accurate information, addressing the specific needs of migrant populations. The design of the evaluation methodology leverages input from experts on social assistance initiatives, social impact and technological solutions, as well as from automated LLM self-evaluations. Given the linguistic challenges specific to the Greek language and the application domain, research findings indicate that Claude 3.7 Sonnet and Gemini 2.0 Flash demonstrate superior performance across all criteria, with Claude 3.7 Sonnet emerging as the leading candidate for the chatbot. Moreover, the results suggest that automated custom evaluations of LLMs can align with human assessments, offering a viable option for preliminary low-cost analysis to assist stakeholders in selecting the optimal LLM based on user and application domain requirements.